2017
DOI: 10.4251/wjgo.v9.i3.105
|View full text |Cite
|
Sign up to set email alerts
|

CpG island methylator phenotype in adenocarcinomas from the digestive tract: Methods, conclusions, and controversies

Abstract: Over the last two decades, cancer-related alterations in DNA methylation that regulate transcription have been reported for a variety of tumors of the gastrointestinal tract. Due to its relevance for translational research, great emphasis has been placed on the analysis and molecular characterization of the CpG island methylator phenotype (CIMP), defined as widespread hypermethylation of CpG islands in clinically distinct subsets of cancer patients. Here, we present an overview of previous work in this field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The existence of tumors characterized by simultaneous hypermethylation of a large number of CpG islands was described in colorectal cancer and called the CpG island methylator phenotype [3]. This molecular phenotype occurs in 15–20% of malignant colorectal tumors [101]. Development of CIMP-positive tumors is associated with elderly age, female gender, higher degree of differentiation and mucinous histological type, localization in the proximal colon, mutations in KRAS or BRAF , and wild-type TP53 [25, 102].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of tumors characterized by simultaneous hypermethylation of a large number of CpG islands was described in colorectal cancer and called the CpG island methylator phenotype [3]. This molecular phenotype occurs in 15–20% of malignant colorectal tumors [101]. Development of CIMP-positive tumors is associated with elderly age, female gender, higher degree of differentiation and mucinous histological type, localization in the proximal colon, mutations in KRAS or BRAF , and wild-type TP53 [25, 102].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt inhibitory factor 1 (WIF1) is a tumor suppressor, which interacts with Wnt protein to inhibit the canonical and non-canonical Wnt pathways. It has been reported that silencing of WIF1 via methylation is associated with cancers, such as colon cancer (6). A previous study additionally reported that WIF1 inhibited the Wnt signaling pathway by inhibiting β-catenin accumulation, suppressed esophageal cancer and decreased the expression of E2F transcription factor 1, cyclin D1 and c-Myc proto-oncogene protein (c-Myc) to promote the apoptosis of hepatoma cells (7).…”
Section: Introductionmentioning
confidence: 98%
“…Cancer-associated CpG island promotor hypermethylation patterns are determined by the tissue of origin [13]. The methylome analysis of our case showed the highest similarity to upper gastrointestinal adenocarcinoma [14]. However, a gastrointestinal primary was never detected.…”
Section: Discussionmentioning
confidence: 85%